Interpretasi Geologi Bawah Permukaan dan Delineasi Cekungan Salawati Wilayah Sorong dan Sekitarnya Berdasarkan Analisis Spektral Serta Pemodelan 2D dan 3D Data Gayaberat - Setiadi, S.Si.,M.T., Imam; Marjiyono, Marjiyono (Pusat Survei Geologi, 2018)
The Salawati Basin is a matured sedimentary basin and hydrocarbon has been produced since 1936. Several oil and gas fields have been produced in carbonate reefs and anticlinal structures. The purpose of this study to determine basement configuration, structure patterns and to delineate the Salawati Subbasin with expecting to predict depocentre and the thickness of sedimentary rocks in this area. Gravity data analysis was done by using spectral analysis, high-low pass filter, 2D and 3D modeling. The result of spectral analysis shows that the average thickness of sedimentary rocks in this research area is 3.4 Km, and the amount of sedimentary subbasin that can be delineated are five subbasins.The most prospect area is around the Sele Strait as a basement high (possibly anticlinal) supplied from two depocentre from the Sele Strait and Klasaman subbasin. The structure pattern that indicated from residual gravity anomaly shows basement high (anticline), transform fault and normal fault. The 2D and 3D modeling results show that the basement in the research areas are metamorphics with density value 2.85 gr/cc, the layer above basement is pre-Tertiary sedimentary rock with density value 2.45 gr/cc, above the pre-Tertiary sediment is Paleogen sedimentary rock with density value 2.5 gr/cc, the top layer is Neogen sedimentary rock with density value 2.35 gr/cc. Based on the data and information, this area is probable attractive for further investigation, especially regarding sedimentary subbasins that make oil and gas can be exploited economically.Keywords : Gravity, spectral analysis, 2D and 3D gravity modeling, Salawati Basin